The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/life11080850
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Memory and Anesthesia: A Systematic Review and Meta-Analysis

Abstract: General anesthesia should induce unconsciousness and provide amnesia. Amnesia refers to the absence of explicit and implicit memories. Unlike explicit memory, implicit memory is not consciously recalled, and it can affect behavior/performance at a later time. The impact of general anesthesia in preventing implicit memory formation is not well-established. We performed a systematic review with meta-analysis of studies reporting implicit memory occurrence in adult patients after deep sedation (Observer’s Assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…We also did not observe implicit recall of the experience, as both responders and non-responders scored similarly on the word retrieval task. Still, implicit recall has been documented in certain conditions during general anaesthesia 28 and could The most significant limitations of this study were the limitations in assessing connected consciousness. Although we assessed IFT responses after tracheal intubation, connected consciousness might occur throughout an anaesthetic and might occur more frequently during maintenance of anaesthesia.…”
Section: Discussionmentioning
confidence: 86%
“…We also did not observe implicit recall of the experience, as both responders and non-responders scored similarly on the word retrieval task. Still, implicit recall has been documented in certain conditions during general anaesthesia 28 and could The most significant limitations of this study were the limitations in assessing connected consciousness. Although we assessed IFT responses after tracheal intubation, connected consciousness might occur throughout an anaesthetic and might occur more frequently during maintenance of anaesthesia.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, the phenomenon of "intraoperative awareness" has been described regularly (Millar and Watkinson, 1983;Ghoneim and Block, 1992;Schwender et al, 1994). However, our results cannot be explained by a few patients reacting like in "intraoperative awareness" with an incidence of only 0.1-0.2% for explicit recall (Sanders et al, 2012) and a few percent for implicit memory (Fu et al, 2021;Linassi et al, 2021). Therefore, auditory impressions that a patient perceives under general anesthesia must be critically questioned, since conversations and noises in the operating room can have a negative influence on patients and should be avoided (Hansen and Zech, 2019).…”
Section: On the Underlying Mechanismmentioning
confidence: 40%
“…For the surgical risk classification, the anesthetic risk categories and the physical status classification according to the American Society of Anesthesiologists (ASA) were used, an important reference for the pre-anesthetic evaluation of the patient [28,29]. Thus, it is used in several studies due to its close relationship with anesthetic morbidity and mortality, as shown in Figure 1.…”
Section: Discussionmentioning
confidence: 99%